Pemberdayaan Warga Kelurahan Klandasan Ilir, Balikpapan, dalam Pengelolaan Lingkungan dan Minyak Jelantah - Siska Ayu Kartika; Muhammad Dani; Ardi Suherman (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Environmental management, especially in this case regarding cleanliness and waste management issues must be a common concern. Community participation must be involved to increase a sense of concern for a clean and healthy environment. This Community Service Activity (PKM) was carried out in Klandasan Ilir, Balikpapan due to several problems related to the lack of awareness and understanding of the community in issues of environmental management, and how to manage household used cooking oil. The method of activities carried out is by identifying the existing problems, generate planning activity programs according to the residents' needs and time, as well as implementing and evaluating the activities carried out. As a result, the residents of Klandasan Ilir have a new understanding of the importance of environmental management and managing used cooking oil that is good for the environment and health, as well as increasing awareness of the importance of cleanliness and preservation of the surrounding environment.